Pseudo-Meigs’ syndrome secondary to breast cancer with ovarian metastasis: a case report and literature review - Lin, Xiang-Ying; Zhou, Xiao-Jun; Yang, Shi-Ping; Zheng, Jia-Xuan; Li, Zhao-Jun (Frontiers in Oncology, 2023)
Ovarian metastasis of breast cancer with pseudo-Meigs’ syndrome (PMS) is extremely rare. Only four cases of PMS secondary to breast cancer with ovarian metastasis have been reported to date. In this report, we present the fifth case of PMS caused by ovarian metastasis of breast cancer. On the 2nd of July 2019, a 53-year-old woman presented to our hospital with complaints of abdominal distension, irregular vaginal bleeding, and chest distress. Color Doppler ultrasound examination revealed a mass approximately 109×89 mm in size in the right adnexal area, accompanied by multiple uterine fibroids and a large amount of pelvic and peritoneal effusions. The patient had no common symptoms and showed no signs of breast cancer. The main manifestations were a right ovarian mass, massive hydrothorax, and ascites. Lab workup and imaging revealed raised CA125 (cancer antigen 125) levels and multiple bone metastases. At first the patient was misdiagnosed with ovarian carcinoma. After the rapid disappearance of oophorectomy hydrothorax and ascites, and decreased CA125 levels, from 1,831.8u/ml to normal range. According to the pathology report, breast cancer was finally diagnosed. The patient underwent endocrine therapy (Fulvestrant) and azole treatment after oophorectomy. At the 40-month follow-up, the patient was still alive and doing well.